Risk of Stroke in Nasopharyngeal Cancer Survivors: A National Registry-Based Population Cohort Study. (11th January 2022) - Tan, Teng Hwee; Zheng, Huili; Cheo, Timothy; Tey, Jeremy; Soon, Yu Yang
Abstract : Background and Objectives: We aim to determine the risk of stroke and death within 30 days after stroke in nasopharyngeal cancer (NPC) survivors. Methods: We conducted a population-based cohort study of patients diagnosed with NPC from January 1, 2005, to December 31, 2017. Using the cancer and stroke disease registries and the Singapore general population as the reference population, we report the age-standardized incidence rate differences (SIRDs) ratios (SIRs) and the cumulative incidence of stroke and the standardized mortality rate differences (SMRDs) and ratios (SMRs) for all causes of death within 30 days after stroke for NPC survivors. Results: At a median follow-up of 48.4 months (interquartile range 19.8–92.9 months) for 3, 849 patients diagnosed with NPC, 96 patients developed stroke. The overall SIRD and SIR for stroke were 3.12 (95% confidence interval [CI] 2.09–4.15) and 2.54 (95% CI 2.08–3.10), respectively. The SIRD was highest for the age group 70 to 79 years old (8.84 cases per 1, 000 person-years, 95% CI 0.46–17.21), while the SIR was highest for the age group 30 to 39 years old (16.41, 95% CI 6.01–35.82). The SIRD and SIR for stage 1 disease were (6.96 cases per 1000 person-years, 95% CI 2.16–11.77) and (4.15, 95% CI 2.46–7.00), respectively. The SMRD and SMR for all cause deaths within 30 days of stroke were (3.20 cases per 100 persons, 95% CI −3.87 to 10.28) and (1.34, 95% CI 0.76–2.37), respectively. Discussion: The overall risk of stroke was markedly elevated in survivors of NPC, especially in stage 1 disease, compared to the general population. The risk of death within 30 days of stroke was not significantly higher for NPC survivors. Classification of Evidence: This study provides Class II evidence of the increased risk of stroke in survivors of NPC compared to the general population.